The Angkatan Hebat Sdn Bhd staffs preparation towards retirement / Uzair Shafeeq Saupin - Saupin, Uzair Shafeeq (2012)
Retirement planning is ever more important in the world today and more so in the future. The increase in the cost of living and economic uncertainties have make it more pressing for people to be more prepared for their retirement. This study is conducted to find out the staffs of the Angkatan Hebat Sdn Bhd preparation towards retirement. This research explores their retirement preparedness and perceptions of retirement and retirement planning.